(untitled) (Pedagogy of Higher and Secondary Education, 2022)
In the article didactic conditions of learning o f symbolism in the course of art culture are defined. Through interpretation of symbolics the mechanism of mastering of knowledge by students of High School is discovered, stages of the information s submission and key images symbols of style are picked out.